A Comparative Analysis of Trademark Rights Protection: Perspectives from Islamic Law and Positive Law in Indonesia - Shuhufi, Muhammad; Firdayanti (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to identify the premise and types of legal protection for trademark rights, comparing Islamic and positive law to explore their roles in safeguarding these rights. Information technology, while aligned with business advancements, can create loopholes for mark violations Irresponsible acts such as brand piracy pose a significant threat to brand proprietors, making trademark rights a major source of civil disputes and illegal acts. This study conducts a comparative analysis of legal literature, focusing on books about Trademark Rights as the primary data source. Data were collected, analyzed, categorized, and conclusions are drawn. The findings showed two forms of legal protection for trademark, which included preventive and coercive. Preventive measures involve government or institutional warnings and restrictions on obligations, while coercive aspects impose penalties on counterfeiters. In Islamic law, forgery is considered the prohibited action of tazyīf, resulting in the infringement of rights of others.